Neurotrophin signaling is a central mechanism of salivary dysfunction after irradiation that disrupts myoepithelial cells - Alejandro M. Chibly; Vaishali Patel; Marit H. Aure; Mary C. Pasquale; Robert J. Morell; Daniel Martin Izquierdo; Erich T. Boger; Gemma E. Martin; Mousa Ghannam; Julianne Andrade; Noah G. Denegre; Colleen Simpson; et al. (2023)
Abstract The mechanisms that prevent regeneration of irradiated (IR) salivary glands remain elusive. Bulk RNAseq of IR versus non-IR human salivary glands showed that neurotrophin signaling is highly disrupted post-radiation. Neurotrophin receptors (NTRs) were significantly upregulated in myoepithelial cells (MECs) post-IR, and single cell RNAseq revealed that MECs pericytes, and duct cells are the main sources of neurotrophin ligands. Using two ex vivo models, we show that nerve growth factor (NGF) induces expression of MEC genes during development, and upregulation of NTRs in adult MECs is associated with stress-induced plasticity and morphological abnormalities in IR human glands. As MECs are epithelial progenitors after gland damage and are required for proper acinar cell contraction and secretion, we propose that MEC-specific upregulation of NTRs post-IR disrupts MEC differentiation and potentially impedes the ability of the gland to regenerate.